2007
DOI: 10.1111/j.1460-9568.2007.05443.x
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative trait locus on chromosome 18 is a critical determinant of excitotoxic cell death susceptibility

Abstract: C57BL/6J (B6) and FVB/NJ (FVB) mice are phenotypically distinct in their susceptibility to seizure-induced cell death after kainate administration. Previous studies using quantitative trait loci (QTLs) mapping established that the distal region of mouse chromosome 18 contains a gene(s) that is probably responsible for the difference in seizure-induced cell death susceptibility between two inbred strains, B6 and FVB, that are relatively resistant and susceptible, respectively, to seizure-induced cell death. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 60 publications
(70 reference statements)
2
28
0
Order By: Relevance
“…These findings suggest that host genetic factors confer protection against hippocampal damage following seizures in resistant strains. Using these mice, we previously identified and confirmed three significant QTL on chromosome 18, 15, and 4 in the mouse genome, responsible for seizure-induced cell death susceptibility through the creation of reciprocal congenic strains and interval-specific congenic lines of mice [19], [20]. The strongest and most significant QTL that determines susceptibility is located on Chr 18 and previous studies have identified galanin receptor type 1 (GalR1) as a compelling candidate gene for the locus on Chr 18 based on expression analyses [21] and its known role as a neuroprotective factor for the hippocampus.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings suggest that host genetic factors confer protection against hippocampal damage following seizures in resistant strains. Using these mice, we previously identified and confirmed three significant QTL on chromosome 18, 15, and 4 in the mouse genome, responsible for seizure-induced cell death susceptibility through the creation of reciprocal congenic strains and interval-specific congenic lines of mice [19], [20]. The strongest and most significant QTL that determines susceptibility is located on Chr 18 and previous studies have identified galanin receptor type 1 (GalR1) as a compelling candidate gene for the locus on Chr 18 based on expression analyses [21] and its known role as a neuroprotective factor for the hippocampus.…”
Section: Introductionmentioning
confidence: 88%
“…Quantitative analysis of hippocampal cell loss was performed in a blinded manned on cresyl violet-stained sections according to previously established protocols [17], [19], [20]. The number of Nissl-stained neuronal profile in areas CA3, CA1, the dentate hilus, and the dentate gyrus were counted in both the right and left hippocampus in horizontal sections for each animal by using four to five Nissl-stained sections that were ∼240 µm apart at the level of the ventral hippocampus.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, hippocampal cell death after seizures and the related molecular mechanisms might not be a general phenomenon, but depend on a complicated interaction between the genetic background and the protocol of seizure induction. Furthermore, while little is known about the distinct factors that cause strain differences in hippocampal vulnerability following seizure induction, modifying genes and quantitative trait loci (QTL) are now recognized as exerting a major influence on regulating the susceptibility to seizure-induced cell death (Kong et al, 2008; Lorenzana et al, 2007; Schauwecker et al, 2004; Schauwecker, 2011). Nevertheless, the genetic basis of variation in seizure-induced cell death remains unclear.…”
Section: Mouse Models Of Epilepsy: Genetic Heterogeneitymentioning
confidence: 99%
“…First, Schauwecker and colleagues (Schauwecker et al, 2004) found a distal region on chromosome 18, that includes the GalR1 locus, houses a quantitative trait locus that significantly influences susceptibility to kainic acid-induced cell death (called,Sicd1). This region was further refined using FVB.B6-Sicd1 lines of mice and the GalR1 locus remained with the region (Lorenzana et al, 2007). Second, recent evidence has demonstrated that GalR1 mRNA is differentially expressed in the hippocampus of sensitive (FVB) and resistant (B6) strains under baseline conditions (Kong et al, 2008;Schauwecker, 2010a).…”
mentioning
confidence: 99%